DAMPAK PEMBELAJARAN ONLINE BERBASIS APLIKASI WHATSAPP GROUP DAN GOOGLE CLASSROOM TERHADAP MOTIVASI BELAJAR DI SDN BRATI 02 - Lestari, Lusiana Fina; Murtono, Murtono; Setiawan, Deka (Universitas Sarjanawiyata Tamansiswa, 2021)
In mid-March 2020, Indonesia was shocked by the emergence of the covid-19, this virus was very dangerous, requiring schools to be temporarily closed, and learning that was usually done face-to-face is now being transferred online. This study aims to determine students learning motivation during e-learning based on the Whatsapp Group application and Google Classroom at SDN Brati 02. This research is qualitative research with a descriptive method, which describes a phenomenon or situation that occurs in a place. The subject is students, student's parents, and teachers of grade 4 SDN Brati 02. Data collection techniques in this study are observation, interviews, and documentation. Data analysis techniques in this study are data reduction, data display, and concluding. The result of this study indicates that e-learning based on the Whatsapp Group application and Google Classroom has an impact on student learning motivation. Ã‚Â